AB0605 Vitamin d serum concentration in european systemic sclerosis patients: correlations with seasonality, organ involvement and standard oral supplementation. (15th June 2017) - Trombetta, AC; Smith, V; Gotelli, E; Ghio, M; Paolino, S; Pizzorni, C; Sulli, A; Cutolo, M
Abstract : Background: Vitamin D deficiency is reported to interfere with immune responses and to correlate with course and outcome in several autoimmune diseases. In systemic sclerosis (SSc), low 25-hydroxyvitamin D (25(OH)D) serum concentration has been recognized. Objectives: To investigate relations between 25(OH)D serum concentration and seasonality, clinical parameters as well as standard oral supplementation, in SSc patients. Methods: 154 SSc patients (mean age 59±15 years, 24.7% diffuse form and 75.3% limited form) were evaluated, at any time of the year, in a retrospective survey. Serum 25(OH)D quantification was performed using the LIAISON 25-OH vitamin D assay (Diasorin, Italy). Pulmonary function test, chest x-ray, lung CT scan, electrocardiography, Doppler echocardiography, renal artery resistive index by eco color Doppler, Dual X-ray absorptiometry, were performed at the time of sample collection. Disease severity scale (DSS) was performed according to Medsger. Drug assumption (glucocorticoids, calcium channel blockers, cyclic intravenous iloprost, endothelin receptor antagonists) and supplementation with vitamin D analogues, were recorded. Non-parametric tests were used for statistical analysis. Results: Average 25(OH)D serum concentration was found to be 18.7±9 ng/ml (<20 classified as deficiency). A significant difference was observed among seasonal 25(OH)D serum concentration (winter: 14.6±7.8 ng/ml, spring: 17.2±7.9 ng/ml, summer 21.43±10 ng/ml, autumn 20.2±10; p =0.032 ) (Figure 1 ). A significant correlation was found between 25(OH)D serum concentration and presence/absence of bi-basal fibrotic changes at lung computed tomography (CT) scan (average values: 16.1±8 ng/ml and 20±10 ng/ml, respectively, p=0.04 ). Peripheral vascular (p=0.03 ), kidney ( p=0.02 ), gastrointestinal ( p=0.05 ) Medsger's DSS parameters also were found to correlate with 25(OH)D serum concentration (Figure 1 ). Interestingly, no influence of treatment with vitamin D analogues (1, 000 UI daily) was found regarding 25(OH)D serum concentration in treated (18.8±10 ng/ml) and in not treated (18.7±9 ng/ml) SSc patients (p=0.81). Conclusions: In SSc is confirmed a serum 25(OH)D deficiency that we report to be associated with lung involvement, peripheral vascular, kidney and gastrointestinal Medsger's DSS parameters, as well as with seasonality. Supplementation with vitamin D analogues did not influence present results. Therefore, for successful replacement, supra-physiological oral vitamin D3 doses or programmed UVB light exposure should be considered. Disclosure of Interest: None declared